Cholesteryl nitrolinoleate, a nitrated lipid present in human blood plasma and lipoproteins - Emersom S. Lima; Paolo Di Mascio; Dulcineia S.P. Abdalla (Journal of Lipid Research, 2003)
Nitric oxide (•NO) and •NO-derived reactive species (e.g., peroxynitrite anion, nitrogen dioxide radical) react with lipids containing unsaturated fatty acids to generate nitrated species. In the present work, we synthesized, characterized, and detected a nitrated derivative of cholesteryl linoleate (Ch18:2) in human blood plasma and lipoproteins using a high-pressure liquid chromatography coupled to electrospray ionization tandem mass spectrometry method. It was synthesized by a reaction of Ch18:2 with nitronium tetrafluoroborate, yielding a species with m/z 711, which is characteristic of the cholesteryl nitrolinoleate (Ch18:2NO2) ammonium adduct. The presence of the nitro group was confirmed by using [15N]nitrite, which gave a product with m/z 712, with the same chromatographic and spectrometric characteristics of those of m/z 711. Furthermore, a C-NO2 structure was also demonstrated in Ch18:2NO2 by infrared analysis (Vmax 1549, 1374 cm−1). A stable product with m/z of 711, showing the same chromatographic characteristics and fragmentation pattern as those of synthesized standard, was found in human blood plasma and lipoproteins of normolipidemic subjects.The presence of this novel nitrogen-containing lipid product in human plasma and lipoproteins could represent a potential indicator of the oxidative/nitrative roles that •NO or its metabolites play during in vivo lipid oxidation, generating a compensatory mechanism of protection in vascular disease.